2010
DOI: 10.1021/jp1096162
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Chemical Raman Enhancement: A Route for Metal Oxide Support-Based Biodetection

Abstract: Raman scattering enhancement was observed in systems where different metal oxide semiconductors (TiO 2 , Fe 2 O 3 , ZrO 2 , and CeO 2 ) were modified with enediol ligands. The intensity of Raman scattering was dependent on laser frequency and correlated with the extinction coefficient of the CT complex of the enediol ligands and nanoparticles. The mechanism of Raman enhancement was studied by varying both the chemical composition of the enediol ligand and the chemical composition (and crystal structure) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
121
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 62 publications
10
121
0
Order By: Relevance
“…In contrast [36], the slower components of emission and fluorescence anisotropy decay are observed for salicylic acid, which forms a comparatively weaker CT complex with TiO 2 nanoparticles, indicating the delocalized nature of the excitation. Additionally, the formation of a CT complex and Raman scattering enhancement for TiO 2 nanoparticles functionalized with salicylic acid was observed by SERS [37,38], although this binding leads to less shifted absorption and a very different Raman spectrum. The Raman signal is lower in intensity than that for the systems employing catecholate-type modifiers, confirming that these are less stable complexes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast [36], the slower components of emission and fluorescence anisotropy decay are observed for salicylic acid, which forms a comparatively weaker CT complex with TiO 2 nanoparticles, indicating the delocalized nature of the excitation. Additionally, the formation of a CT complex and Raman scattering enhancement for TiO 2 nanoparticles functionalized with salicylic acid was observed by SERS [37,38], although this binding leads to less shifted absorption and a very different Raman spectrum. The Raman signal is lower in intensity than that for the systems employing catecholate-type modifiers, confirming that these are less stable complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have investigated CT complex formation between catecholate [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and salicylate [27,[36][37][38]40,41] type ligands and colloidal TiO 2 nanoparticles (d $ 45 Å), where the binding of modifiers induces the surface reconstruction of the nanoparticles. Recently, combined theoretical (DFT) and experimental studies were performed, mainly on catecholate-type molecules as surface modifiers of rutile [32] and anatase [33][34][35] TiO 2 nanoparticles, reporting different adsorption geometries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented in literature that titania binds strongly with the catechol groups of dopamine in a bidentate geometry [34]. The solid-state UV analysis of the Pdop/TiO 2 support showed the ligand-to-metal charge transfer complex formation between TiO 2 and catechol groups [35] extended the absorption into the visible light region as apparently indicated by the color change (Fig. S10).…”
Section: Como Supported On Pdop Coated Titania and Its Catalytic Actimentioning
confidence: 55%
“…3,[10][11][12][13] And more recently, other systems involving either a metal oxide thin film or a hybrid system of a metal nanoparticle/metal oxide thin film have been demonstrated as SERS-active materials. 7,[14][15][16][17][18][19] Plasmonic characteristics similar to those observed from noble metals are found in some transparent conducting metal oxides such as indium tin oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide. 18,20 Despite many leading efforts on this aspect, only a small subset of research discusses Raman enhancement effects observed from nanomaterials that are precisely controlled for their physical, chemical, optical, or electrical properties during synthesis.…”
mentioning
confidence: 60%